Atlantic Forest streams and landscapes : biodiversity and environmental education. - Scoarize, Matheus Maximilian Ratz (2024)
Due to the intense biodiversity and habitat loss caused by human activities in the last centuries, this moment has been named biological annihilation period. From the original Atlantic Forest, a biodiversity hotspot in Brazil, just 28% remains, and only 9%ispreserved in protected areas. Among the causes, land use change is a major one, original native vegetation is often converted into anthropogenic land use, destroying habitats. Rooted in this scenario, studies have tested whether this change may cause biotic homogenisation. Moreover, disturbances in the landscape and environmental conditions may remove or add links from the food chain, disturbed ecosystems could present shorter food chains, for example. Among the mitigation strategies, environmental education plays a pivotal role. However, considering the influence that landscape has over the environment, one might ask whether it also affects people from different backgrounds. Do rural communities have a better environmental perception than urban dwellers? Thus, we aimed to investigate how biodiversity patterns are affected by different land uses in the watershed; whether the food chain is affected by land use; whether landscape affects people’s environmental perception; and whether a single act of environmental education could change the perception of students. Therefore, we sampled and analysed data from seventeen streams and nearby schools, in rural, urban and protected land uses. Our results showed that biotic homogenisation does not explain them, but species composition and dominance suggest that the Atlantic Forest could already be homogenised. Also, the food chain length was affected by disturbance, thus disturbances in the landscape play a role in the freshwater ecosystems. Moreover, landscape plays a role in students’ environmental perception, peripheral students showed lower scores compared to other groups (e.g. rural). And finally, a single act of environmental education can indeed change students’ perception, thus, there is hope. Based on our results, we suggest that conservation authorities start i) monitoring and communicating conservation indicators, and also ii) investing in restoration of riparian vegetation. Furthermore, environmental education is a conservation key, and even a single act can increase students’ environmental perception. Thus, a regional program of environmental education should be developed and implemented, focusing on native biota, landscape conservation and human-nature connectedness.